More nights than days : a survey of writings of child genocide survivors - Kiss, Judit (Central European University Press, 2023)
"More Nights Than Days is a unique exploration of the experience of children who survived the Holocaust-including Roma and Sinti victims-and the genocides in Cambodia, Rwanda, and Bosnia. Children are among the principal victims of armed conflicts and slaughters; nonetheless, they perceive events through the prism of their unique perspective and have a range of coping techniques adults don't possess.This overview of writings of ninety-one child survivors bears evidence from a wide range of human ruthlessness. The author presents little-known texts along with famous memoirs and autobiographical fiction, with abundant quotations. Many of these are not only compelling as historical testimony, but poetic and stirringly expressive. Yudit Kiss has not written a historical study or literary criticism of the children's books. She explores, instead, what the authors went through and what they felt and understood about their experience. An accessible and captivating reading, this volume presents a close-up, human size dimension of the destruction. The books written by child survivors also describe the resources and means that helped them to remain human even in the deepest well of inhumanity, offering precious lessons about resistance and resilience"--